Pengaruh Pemberian Pakan Konsentrat dengan Sawi Hijau dan Daun Singkong terhadap Pertumbuhan dan Produktivitas Jangkrik - Anie Yuni Widyastuti; Harlita Harlita (Universitas Sebelas Maret, 2023)
The study aims to determine the effect of feeding additional ingredients in concentrate with mustard greens (Brassica rapa) and cassava leaves (Manihot esculenta) on cricket growth and egg productivity. The study used an experimental method of Completely Randomized Design (CRD) with three treatments: control (P0) with concentrate feeding, P1 with concentrate plus green mustard and P2 concentrate plus cassava leaves with a total of 24 crickets per treatment. The research was conducted form September-October 2023 with two stages. The first stage was carried out with additional feed treatment to measure cricket growth (length and weight) for 35 days. The second stage measured cricket egg productivity with the same feeding treatment for seven days after mating. Data analysis of cricket growth with One Way Anova using SPSS 25. The results showed that cricket growth was not significantly different in each treatment, and in P1, the highest egg productivity was obtained.